Implementasi Penanganan Perkara Membujuk Anak Melakukan Persetubuhan Oleh Anak (Studi Perkara Nomor : LP/B/06/2024/SPKT/POLRESINHIL) - Fani H; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This research aims to determine the implementation of handling cases of persuading a child to commit sexual intercourse by a child in Case Number LP/B/06/2024/SPKT/Polres Inhil, to identify the obstacles faced by investigators in handling the case, and to examine the efforts made to overcome these obstacles in accordance with child protection principles and the Juvenile Criminal Justice System. The research method used is empirical legal research with a socio-juridical approach, which examines legal provisions and their implementation in practice. The results show that the handling of the case is carried out through investigation and inquiry stages based on criminal procedural law and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System while considering the rights of children in conflict with the law. The obstacles faced by investigators include difficulties in the evidence process, children's psychological conditions, limited human resources, and coordination with related institutions. Efforts made to overcome these obstacles include conducting child-friendly examinations, involving probation officers, providing legal assistance, and strengthening coordination among institutions to ensure child protection and law enforcement in accordance with the principles of the Juvenile Criminal Justice System